Balloon valvuloplasty in the treatment of congenital aortic valve stenosis - a retrospective multicenter survey of more than 1000 patients - Ewert, Peter; Bertram, H.; Breuer, J.; Dähnert, I.; Dittrich, S.; Eicken, A.; Emmel, M.; Fischer, G.; Gitter, R.; Gorenflo, Matthias; Haas, N.; Kitzmüller, E.; et al. (International journal of cardiology, 2011)
Background - The value of balloon valvuloplasty of the aortic valve in childhood is still under debate. - Objective - To evaluate the results of the procedure in a retrospective multicenter survey of a large cohort over a long time interval. - Methods - Retrospective analysis of 1004 patients with balloon valvuloplasty of the aortic valve performed between 9/1985 and 10/2006 at 20 centers in Germany, Austria and Switzerland. Amongst others, the following parameters were evaluated before and after the procedure as well as at the end of follow-up or before surgery: clinical status, left ventricular function, transaortic pressure gradient, degree of aortic regurgitation, freedom from re-intervention or surgery. - Patients - Patients from 1day to 18years of age with aortic valve stenosis were divided into four groups: 334 newborns (1-28days); 249 infants (29-365days); 211 children (1-10years), and 210 adolescents (10-18years). - Results - Median follow-up was 32months (0days to 17.5years). After dilatation the pressure gradient decreased from 65 (±24)mm Hg to 26 (±16)mm Hg and remained stable during follow-up. The newborns were the most affected patients. Approximately 60% of them had clinical symptoms and impaired left ventricular function before intervention. Complication rate was 15% in newborns, 11% in infants and 6% in older children. Independently of age, 50% of all patients were free from surgery 10years after intervention. - Conclusions - In this retrospective multicenter study, balloon valvuloplasty of the aortic valve has effectively postponed the need for surgery in infants, children and adolescents up to 18years of age.